IMPLEMENTATION OF INTERACTIVE LEARNING MEDIA THROUGH SMART MUSLIM SPINNER (SMS) IN ISLAMIC RELIGIOUS EDUCATION SUBJECT FOR GRADE V STUDENTS OF SD N 1 KUBANG BANJARNEGARA - Yayu Konita Istiqomah; Firdaus; Pamungkas Stiya Mulyani (Alphateach (Jurnal Profesi Kependidikan dan Keguruan), 2026)
This study examines the implementation of the Smart Muslim Spinner (SMS), an interactive learning medium, in Islamic Religious Education (IRE) learning for Grade V students at SD N 1 Kubang Banjarnegara. The study addresses the need for engaging learning media to increase student participation and understanding of IRE material. A qualitative descriptive approach with a field research design was employed. Data were collected through observation, in-depth interviews, and documentation involving the IRE teacher and Grade V students. Data were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that the implementation of SMS consisted of three stages: preparation, classroom implementation, and assessment of learning outcomes. The use of SMS created a more interactive and engaging learning environment by involving students in game-based question-and-answer activities. Students demonstrated greater enthusiasm, participation, and focus during lessons, while the play-based learning process facilitated their understanding of the material. Supporting factors included teacher readiness, innovative instructional design, and student motivation. Challenges encountered were increased classroom noise and the need for regular maintenance of the learning medium. The study concludes that the Smart Muslim Spinner is an effective alternative interactive learning medium for Islamic Religious Education at the elementary school level, as it promotes active participation and supports students’ comprehension of learning materials